PENGARUH SISTEM AKUNTANSI PIUTANG DAN PENERIMAAN KAS SEBAGAI ALAT PENGENDALIAN INTREN PADA PT. FEDERAL INTERNASIONAL FINANCE (FIF) - Effendi, Syahril (Universitas Riau Kepulauan, 2015)
On FIF Corporation Batam, account receivable system destine to record the mutation of the company receivable of the debtors. The receivable mutation was caused by the credit selling transaction, the cash acceptance of the debtors. Because of that, the FIF Corporation Batam is expected to have a better system to help the controlling, because the internal check mechanism will be committed as it is during the company activities is going on. The data collecting technic used by the writer through the documentation, observation, interview and questioner, while the analysis technic used is Descriptive Analysis Technic.Through the research system of the account receivable does not influence the internal controlling on FIF significantly, the sig value 0,000 or 0,05. Therefore, cash acceptance accounting system impact significantly to the internal controlling on FIF dan nilai F 346.377 with sig. 0.000 or the value sig 0,05. So, the account receivable system and cash acceptance impact significantly to the internal controlling on FIF.Keyword : Account Receivable System, Cash Acceptance Accounting System and Internal Controlling